Predictors of Language Proficiency among Medical and Paramedical Students: Vygotskian Sociocultural Theory - Shadab Moslehi; Reza Kafipour (National Research University Higher School of Economics, 2023)
Background: There are many factors in determining language proficiency among university students. Identifying these factors can help the teaching and learning process to move forward more quickly and effectively. Purpose: This study aimed to explore the relationship between social, cultural, and linguistic factors and the language proficiency of 221 medical and paramedical students at Shiraz University of Medical Sciences to identify if these factors contribute to language proficiency as an effective variable in students' communication, academic performance, and quality patient care. Method: The authors administered a questionnaire on these factors' role and a proficiency test. Then, they ran Pearson's correlation coefficient and multiple regression analyses to determine the relationship and effects of such factors concerning language proficiency. Results: The t-test revealed a statistically meaningful difference between medical and paramedical students concerning both mean scores of proficiency and cultural factors. The results indicated only social and cultural factors statistically correlated with paramedical students' proficiency. Furthermore, none of these factors built any relationship or exerted any effects on the proficiency of medical students. Conclusion: The results implied that educational policymakers should consider the existing differences between university students of different fields since they come from different sociocultural and linguistic backgrounds that have affected the academic stance in which they are studying. Moreover, the findings necessitate encouraging the policymakers and university lecturers to enhance their sociocultural competencies to adapt and fulfill the needs of such students and highlighting the roles of the family's socioeconomic positions through some workshops since the role of the family is an important variable in determining the extent to which a learner has acquired a specific cultural competence.